Pregunta
upstudy study bank question image url

Solve \[ \begin{array}{l}-4 x-10 y=-2 \\ -4 x-6 y=2\end{array} \]

Ask by Salinas Henry. in the United States
Feb 28,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The solution is \( x = -2 \) and \( y = 1 \).

Solución

Solve the system of equations \( -4x-10y=-2;-4x-6y=2 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}-4x-10y=-2\\-4x-6y=2\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=\frac{1-5y}{2}\\-4x-6y=2\end{array}\right.\) - step2: Substitute the value of \(x:\) \(-4\times \frac{1-5y}{2}-6y=2\) - step3: Simplify: \(-2+4y=2\) - step4: Move the constant to the right side: \(4y=2+2\) - step5: Add the numbers: \(4y=4\) - step6: Divide both sides: \(\frac{4y}{4}=\frac{4}{4}\) - step7: Divide the numbers: \(y=1\) - step8: Substitute the value of \(y:\) \(x=\frac{1-5\times 1}{2}\) - step9: Substitute back: \(x=\frac{1-5}{2}\) - step10: Calculate: \(x=-2\) - step11: Calculate: \(\left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\) - step12: Check the solution: \(\left\{ \begin{array}{l}x=-2\\y=1\end{array}\right.\) - step13: Rewrite: \(\left(x,y\right) = \left(-2,1\right)\) The solution to the system of equations is \( (x,y) = (-2,1) \).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To solve the system of equations \[ \begin{array}{l} -4x -10y = -2 \quad (1)\\ -4x -6y = 2 \quad (2) \end{array} \] we can start by eliminating one variable. We can do this by subtracting equation (2) from equation (1). Starting with: \[ (-4x - 10y) - (-4x - 6y) = -2 - 2 \] This simplifies to: \[ -4y = -4 \] Dividing both sides by -4 gives us: \[ y = 1 \] Now we can substitute \(y = 1\) back into either original equation; let's use equation (2): \[ -4x - 6(1) = 2 \] This simplifies to: \[ -4x - 6 = 2 \] Adding 6 to both sides gives: \[ -4x = 8 \] Dividing both sides by -4 results in: \[ x = -2 \] Thus, the solution to the system of equations is: \[ (x, y) = (-2, 1) \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad